2005
DOI: 10.1093/jnci/dji401
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress and Susceptibility to Skin Cancer

Abstract: Chronic stress increased susceptibility to UV-induced squamous cell carcinoma in this mouse model by suppressing type 1 cytokines and protective T cells and increasing regulatory/suppressor T cell numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
163
0
10

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(176 citation statements)
references
References 49 publications
3
163
0
10
Order By: Relevance
“…Perhaps most contentious is the apparent association between stressful events and skin cancer. Interestingly, chronic stress has been shown to increase susceptibility to UV-induced SCC in mice, 47 and more than 50% of a group of 75 patients with CMM reported at least one episode of major stress in the 5 years prior to diagnosis. 48 A potential mechanism is that chronic stress negatively affects many physiological processes through prolonged exposure to elevated levels of glucocorticoids and catecholamines 19 or as negative effects on natural killer cell and T-cell function relevant for tumour immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps most contentious is the apparent association between stressful events and skin cancer. Interestingly, chronic stress has been shown to increase susceptibility to UV-induced SCC in mice, 47 and more than 50% of a group of 75 patients with CMM reported at least one episode of major stress in the 5 years prior to diagnosis. 48 A potential mechanism is that chronic stress negatively affects many physiological processes through prolonged exposure to elevated levels of glucocorticoids and catecholamines 19 or as negative effects on natural killer cell and T-cell function relevant for tumour immunity.…”
Section: Discussionmentioning
confidence: 99%
“…23 In mice, chronic stress has been shown independently to suppress immunity and may contribute to skin cancer risk or enhance tumour growth. 47,49,50 Stress can also affect the cellular process involved in the repair of damaged DNA 51,52 and could thereby facilitate the establishment of oncogenic UV-induced mutations as an additional mechanism. Although it is difficult to refute the potential for recall bias in this study, there is growing evidence that stressful experiences may be a very real risk factor for cancer in general and, in this case, for all three types of skin cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of "cancer proneness," "cancerous personality" or "personality susceptible to immunosuppression" assumes the tendency to repress emotional reactions to difficult life events (Dattore et al, 1980;Eysenc, 1985;Watson, Pettingale, & Greer, 1984). The researchers explain greater incidence of cancer among repressors by the impaired reaction of immune defense and by the hormonal changes as a result of long maintenance of stress due to inhibited expression of dissatisfaction and, in parallel, ineffective coping with stressors (KiecoltGraser, & Glaser, 1986;Penedo et al, 2006;Reiche, Nunes, & Morimoto, 2004;Saul et al, 2005;Septon, & Spiegel, 2003;Zorrilla, Luborsky, & McKay, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…26, 41 Saul et al 42 demonstrated in animal experiments that chronic stress caused the suppression of type I cytokines, reduction of T-helper cell counts and increased T-suppressor cell numbers together with enhanced susceptibility to UV-induced squamous cell carcinoma. Repeated exposure to stress can thus lead to an increase in regulatory T cells in UV-induced skin cancer and may thus be among the reasons for the observed increase in T-regulatory function in melanoma patients.…”
Section: Neuroendocrine-immune Interaction and Skin Cancer Control: Tmentioning
confidence: 99%